Influence of milk pre-treatment on production of FFA and volatile compounds in hard cheeses: heat treatment and mechanical agitation. - Vélez, María Ayelén (2010)
This work was aimed at identifying technological steps that can increase fat hydrolysis and volatile compounds production in hard cheeses, as these biochemical events have been related with improved piquant taste and development of genuine flavour during cheese ripening. For that purpose, two different pre-treatments of cheese-milk were tested: heat treatment and mechanical agitation. Both factors were assayed at two levels: milk was both batch-pasteurized or non-thermally treated, and mechanical agitation was either applied or not. With pre-treated or not milk, hard cheeses (Reggianito type) were produced in pilot plant and ripened during 90 days. In all cheeses it was observed that the degree of lipolysis, assessed by gas chromatography (GC-FID), increased similarly during ripening. However, the proportion of short chain fatty acids (SCFA) was higher in the cheeses made with unpasteurized milk, suggesting a higher activity of lipases with positional specificity towards the sn-3 position of the triglyceride, among which milk lipoprotein lipase is found. Similar results were found for most of the volatile compounds, determined by SPME-GC-FID/MS, which constitute the groups of ketones, alcohols, esters and the group of acids. On the contrary, no effect of mechanical agitation was observed although some interactions between factors were found. In the conditions of the study, results suggest that heat treatment had a higher impact on cheese lipolysis and volatile compounds production than partial destabilization of the fat emulsion produced by the agitation method applied.